O2 selective membranes based on a dextrin-nanosponge (NS) in a PVDF-HFP polymer matrix for Li–air cells. Issue 94 (7th November 2016) - Amici, J.; Alidoost, M.; Francia, C.; Bodoardo, S.; Martinez Crespiera, S.; Amantia, D.; Biasizzo, M.; Caldera, F.; Trotta, F.
Abstract : A novel oxygen selective highly hydrophobic membrane is prepared by non-solvent induced phase separation in which a dextrin-based nanosponge is incorporated into a PVDF-HFP matrix. Abstract : A novel oxygen selective highly hydrophobic membrane is prepared by non-solvent induced phase separation in which a dextrin-based nanosponge is incorporated into a poly(vinylidene fluoride co -hexafluoropropylene) (PVDF-HFP) matrix. The membrane presents high capability to entrap moisture from air as well as good hydrophobic behaviour. The membrane was assembled in a pouch type Li–air cell, which was cycled in a galvanostatic mode at curtailed capacity, in air with 17% relative humidity (RH). Owing to the protection of the membrane, the Li–air cell was able to discharge and re-charge for approximately 145 cycles, which correspond to about 1450 h of cell operation.